Genetic interplay between human longevity and metabolic pathways — a large‐scale eQTL study - Häsler, Robert; Venkatesh, Geetha; Tan, Qihua; Flachsbart, Friederike; Sinha, Anupam; Rosenstiel, Philip; Lieb, Wolfgang; Schreiber, Stefan; Christensen, Kaare; Christiansen, Lene; Nebel, Almut (Aging cell, 2017)
Summary Human longevity is a complex phenotype influenced by genetic and environmental components. Unraveling the contribution of genetic vs. nongenetic factors to longevity is a challenging task. Here, we conducted a large‐scale RNA‐sequencing‐based expression quantitative trait loci study (eQTL) with subsequent heritability analysis. The investigation was performed on blood samples from 244 individuals from Germany and Denmark, representing various age groups including long‐lived subjects up to the age of 104 years. Our eQTL‐based approach revealed for the first time that human longevity is associated with a depletion of metabolic pathways in a genotype‐dependent and independent manner. Further analyses indicated that 20% of the differentially expressed genes are influenced by genetic variants in cis. The subsequent study of twins showed that the transcriptional activity of a third of the differentially regulated genes is heritable. These findings suggest that longevity‐associated biological processes such as altered metabolism are, to a certain extent, also the driving force of longevity rather than just a consequence of old age.